Identifikasi Pelayanan Promotif pada Fasilitas Kesehatan Tingkat Pertama Program Jaminan Kesehatan Nasional (Identification of Promotive Services In Primary Health Care Facility of National Health Insurance Program) - Ratih Kumala Dewi; Nuryadi Nuryadi; Christyana Sandra (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Promotive services is important to support the enactment of the National Health Insuranceprogram, for any medical expenses that are collected through dues, it will run out if notaccompanied by increased promotional efforts. Based on preliminary studies were conductedto the Primary Health Care Facility in Jember district, data obtained 6 (40%) Primary HealthCare Facility who carry out services Promotive, It indicate that Primary Health Care Facilitydoing promotive still low in Jember district, The purpose of this study was to identify Promotiveservices in Primary Health Care Facility of the National Health Insurance Program. Thisresearch is descriptive. This study was conducted in Primary Health Care Facility in Jemberdistrict in November 2015. The samples were 30 Primary Health Care Facility. The resultsshowed a large majority has not made promotive, Input Element, human resources PrimaryHealth Care Facility no one had a special officer to promotive services. The level of knowledgeof the entire head Primary Health Care Facility had a high level of knowledge. No PrimaryHealth Care Facility that allocate costs to promotive services. Funds used for service prolanisof funds claim to the Social assurance agency. Most goals Primary Health Care Facility thatindividuals and groups using the method of counseling and lectures as well as the majority useprint media that leaflet. While the place promotive services carried out in the institution building.Most of the elements of the process had not been doing.Keywords: Promotive services, National Health Insurance.